2021
DOI: 10.3389/fonc.2020.594342
|View full text |Cite
|
Sign up to set email alerts
|

Survival Status of Esophageal Cancer Patients and its Determinants in Ethiopia: A Facility Based Retrospective Cohort Study

Abstract: BackgroundGlobally, the incidence and mortality due to esophageal cancer are increasing, particularly in low- and middle-income countries. Cancer of the esophagus is the eighth in incidence and seventh in cancer mortality in Ethiopia. A few studies have shown an increasing burden, however, little is known about the survival pattern and its determinants among esophageal cancer patients in Ethiopia. Therefore, we assessed the survival pattern and its determinants among esophageal cancer patients.MethodsWe conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…Furthermore, Cox's proportional hazards regressions were performed to investigate the survival pattern and determinants of cancer-specific mortality among colorectal, esophageal and prostate cancer patients. Detailed results including Kaplan-Meier survival curves are available elsewhere [2] , [3] , [4] . We also performed a life table analysis for each cancer within five months of interval and the results are summarized in this article.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Cox's proportional hazards regressions were performed to investigate the survival pattern and determinants of cancer-specific mortality among colorectal, esophageal and prostate cancer patients. Detailed results including Kaplan-Meier survival curves are available elsewhere [2] , [3] , [4] . We also performed a life table analysis for each cancer within five months of interval and the results are summarized in this article.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…To comply with the ethical standards, identifiers such as name, medical registration number, physical address and telephone numbers are excluded from the datasets. Details of the analyzed data including sociodemographic characteristics, survival curves, and determinants of mortality among colorectal, esophageal and prostate cancer patients are available elsewhere [2] , [3] , [4] . Life table analyzes were computed for each cancer and the results are presented in this paper.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Patients who underwent esophagectomy, radiotherapy, or chemoradiation had no differences in mean survival estimates compared to their counterparts. In contrast, an Ethiopian study revealed a better survival outcome, although most patients had low overall survival 35 . In addition, a previous study shows a relatively low overall rate of survival, although surgically treated patients had a significant improvement in survival outcomes 40 .…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, an Ethiopian study revealed a better survival outcome, although most patients had low overall survival. 35 In addition, a previous study shows a F I G U R E 2 Kaplan-Meier survival curve of esophageal cancer patients with comorbidities and distant metastasis DETERMINANTS OF SURVIVAL OUTCOMES relatively low overall rate of survival, although surgically treated patients had a significant improvement in survival outcomes. 40 In our setting, chemotherapytreated patients had the longest duration of mean survival estimates compared to other treatment modalities suggesting possible priorities in eligible esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…Esophageal cancer is the seventh most common cancer globally, with more than 500,000 cases annually contributing to over 500,000 cancer deaths per year [ 22 ]. Esophageal cancer incidence and mortality are increasing in developing countries [ 23 , 24 ]. On the African continent, both the South and East have high numbers of cases and mortality [ 25 ].…”
Section: Introductionmentioning
confidence: 99%